2021
DOI: 10.1002/jssc.202001128
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of tiafenacil in five types of citrus orchard soils using the HPLC‐MS coupled with the quick, easy, cheap, effective, rugged, and safe method

Abstract: Tiafenacil is a new contact herbicide and its environmental behavior after field application remains poorly understood. In order to understand the dissipation of tiafenacil in the soil, the tiafenacil dissipation experiment was conducted at citrus orchard sites in five provinces of China (Gansu, Shandong, Sichuan, Jiangxi, and Hainan) in 2019 and 2020 (July-August) and the relevant determination methods were optimized. The results showed that the established method showed good linearity in the concentration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…ME refers to the difference between the mass spectrometric response of analyte in neat solvent and the response of the same analyte in the matrix, resulting from the alteration of ionization efficiency of target analytes in the presence of co-eluting compounds. MEs can be calculated by the following Equation (1) [24]:…”
Section: Methods Validationmentioning
confidence: 99%
“…ME refers to the difference between the mass spectrometric response of analyte in neat solvent and the response of the same analyte in the matrix, resulting from the alteration of ionization efficiency of target analytes in the presence of co-eluting compounds. MEs can be calculated by the following Equation (1) [24]:…”
Section: Methods Validationmentioning
confidence: 99%
“…The dry root donor-part of Peucedanum praeruptorum Dunn is currently used in traditional Chinese medicine, exerting an effect on exogenous wind-heat; lung heat and phlegm depression; cough, asthma, and phlegm; and tightness in the chest and diaphragm (1). The root of Peucedanum praeruptorum Dunn contains a variety of coumarin compounds and these active substances are also independently used in health products (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the simultaneous analysis of the above nine TKIs using HPLC–diode array detection (DAD) required a running time of 17.5–35 min [8–11]. LC–MS and LC–MS/MS have high analytical SEN [12–14]. However, they are expensive, have high maintenance costs, and need professional technicians to operate.…”
Section: Introductionmentioning
confidence: 99%